Changes in elite Canadian collegiate hockey player`s body compositions and physiological tests across three-year University careers - Chiarlitti, N. A.; Delisle-Houde, P.; Reid, R. E. R.; Andersen, R. E. (Biology of Exercise, 2019)
Given that body composition is an important factor in hockey performance, monitoring changes from season to season may help coaches optimize player performance. Male Canadian colligate hockey players (n = 34) underwent one total body dual energy x-ray absorptiometry scan to assess body composition at the beginning of each season over the course of their collegiate hockey careers. Additionally, a sub-sample of ten players were followed through their first three years in collegiate hockey. Typically, players gained body mass, total body fat, and regional fat throughout their first four seasons. Regional and total body lean tissue mass stayed relatively constant. Similarly, in the subsample of players, a repeated measures ANOVA revealed that as players progressed through their careers, they gained body mass, and body fat percentage from season 1 to season 2 (p < .05), but not in season 3. A similar pattern was observed in upper and lower body fat, but not regional or total body lean tissue mass. With these findings, strength and conditioning coaches can work in tandem with food scientists and dietitians in an effort to prevent adipose tissue gain which may be mitigating onice performance and player health across university careers.